The Influence of Self-Confidence and Economic Status on Adolescent Career Development in Industrial Career Guidance - Ria Marsela; Tina Anggriani; Rahmah Rahmah; Karyanti Karyanti; Asep Solikin (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: The dynamics of industrial development require adolescents to develop strong career-readiness from an early age, including self-confidence and a clear career orientation, as essential capital to face job-market competition. Aim: This study aims to describe levels of self-confidence and career development among adolescents and to examine differences in their distribution by family economic status. Method: The research employed a quantitative, descriptive-observational design, using a cross-sectional survey of adolescents from diverse economic backgrounds. The research instruments consisted of Likert-scale questionnaires to measure levels of self-confidence and career development, as well as demographic data related to family economic status. Results and Discussion: The results indicate that the majority of respondents exhibit moderate to high levels of self-confidence and career development, both overall and across economic status. The discussion emphasizes that psychosocial factors play a more dominant role than economic aspects in supporting career readiness. Conclusion: The study concludes that industrial Career Guidance services should be equitably oriented toward strengthening adolescents' self-confidence and career exploration skills. Further research is recommended to examine relationships among variables using inferential designs and to develop more comprehensive career guidance interventions across various educational settings.